Cultural adaptation and validation of the Arabic version of the short 12-item stroke-specific quality of life scale - Sakr, Fouad; Dabbous, Mariam; Akel, Marwan; Salameh, Pascale; Hosseini, Hassan (Frontiers in Neurology, 2023)
Background: Given the excessive length and inconsistent validity of the existing long stroke-specific quality of life (SS-QOL) scales, there is a need to validate a shorter measuring tool. The aim of this study was to validate the Arabic version of the short 12-item SS-QOL (SS-QOL-12-AR) and examine its validity measures and psychometric properties. Additionally, the study aimed to assess the QOL after stroke and identify the sociodemographic and clinical factors that influence it in Lebanon. Methods: A cross-sectional study was conducted. The SS-QOL-12-AR structure was validated, and its reliability and internal consistency were assessed. The scale’s specificity and sensitivity were evaluated and then compared with those of other SS-QOL scales. The correlation between each item and the overall scale were examined, and its convergent validity was evaluated. Results: A total of 172 stroke survivors were included. The SS-QOL-12-AR structure was validated with a solution of two factors, with a Kaiser-Meyer-Olkin measure of sampling adequacy of 0.850 and a significant Bartlett’s test of sphericity (P < 0.001). The Cronbach’s alpha of the scale was 0.917. According to ROC curve analysis, the optimal cut-off point for distinguishing between lower and better QOL was 32.50. At this cut-off, the sensitivity and specificity were 70.0% and 71.2%, respectively. The area under the curve was 0.779 (95% CI 0.704 – 0.855, P < 0.001). The SS-QOL-12-AR demonstrated a strong and highly significant correlation with existing versions of the SS-QOL, confirming its convergent validity. 61.6% of stroke survivors had a lower QOL, which was significantly associated with poor stroke prognosis, increased physical dependence, current smoking, and alcohol abstinence. Conclusion: The SS-QOL-12-AR exhibits strong validity and reliability, demonstrating excellent psychometric properties. The scale holds potential for application in clinical practice and research settings, enabling the measurement of stroke-related consequences and evaluation of management outcomes.